Use of a capacitance influence probe for measuring wave profiles - Phillips, J. E., author; Schulz, Edmund F., author; Colorado State University, Civil Engineering Section, publisher (Colorado State University. Libraries, 1958)
This report describes the features of electronic instrumentation for measuring and recording the wave amplitudes and configurations of water waves. The gaging element of this system consists of a small flat metal plate suspended above the surface of the water. This plate acts as one plate of a capacitor and the surface of the water acts as the other plate. The dielectric of this capacitor is the air space between the water and the probe plate. The capacitance of this unit is an inverse function of the distance between the water and the probe plate. The capacitor is connected in a resonant circuit which oscillates in the region of 7 megacycles. This frequency is changed by the variation in capacitance between the water and the probe unit and is eventually discriminated and fed into a recording galvanometer. This report includes schematic and block diagrams of the instrument and data gathered in the process of design and development of the various component parts.
CER58EFS-3.
Prepared for David Taylor Model Basin, Navy Department through the Colorado State University Research Foundation.
Keywords: Water waves -- Measurement -- Equipment and supplies